Ceftriaxone and Melittin Synergistically Promote Wound Healing in Diabetic Rats - Nabil A. Alhakamy; Giuseppe Caruso; Basma G. Eid; Usama A. Fahmy; Osama A. A. Ahmed; Ashraf B. Abdel-Naim; Abdulmohsin J. Alamoudi; Shareefa A. Alghamdi; Hadeel Al Sadoun; Basmah M. Eldakhakhny; Filippo Caraci; Wesam H. Abdulaal (MDPI AG, 2021)
High glucose levels in diabetic patients are implicated in delay wound healing that could lead to more serious clinical complications. The aim of the present work was to examine the formulation of ceftriaxone (CTX) and melittin (MEL) as nanoconjugate (nanocomplex)-loaded hydroxypropyl methylcellulose (HPMC) (1.5% w/v)-based hydrogel for healing of acute wounds in diabetic rats. The CTX-MEL nanoconjugate, formulated by ion-pairing at different molar ratio, was characterized for size and zeta potential and investigated by transmission electron microscopy. CTX-MEL nanoconjugate was prepared, and its preclinical efficacy evaluated in an in vivo model of acute wound. In particular, the potential ability of the innovative CTX-MEL formulation to modulate wound closure, oxidative status, inflammatory markers, and hydroxyproline was evaluated by ELISA, while the histopathological examination was obtained by using hematoxylin and eosin or Masson's trichrome staining techniques. Quantitative real-time PCR (qRT-PCR) of the excised tissue to measure collagen, type I, alpha 1 (Col1A1) expression and immunohistochemical assessment of vascular endothelial growth factor A (VEGF-A) and transforming growth factor beta 1 (TGF-β1) were also carried out to shed some light on the mechanism of wound healing. Our results show that the CTX-MEL nanocomplex has enhanced ability to regenerate epithelium, also giving better keratinization, epidermal proliferation, and granulation tissue formation, compared to MEL, CTX, or positive control. The nanocomplex also significantly ameliorated the antioxidant status by decreasing malondialdehyde (MDA) and increasing superoxide dismutase (SOD) levels. The treatment of wounded skin with the CTX-MEL nanocomplex also showed a significant reduction in interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) pro-inflammatory cytokines combined with a substantial increase in hydroxyproline, VEFG-A, and TGF-β1 protein expression compared to individual components or negative control group. Additionally, the CTX-MEL nanocomplex showed a significant increase in mRNA expression levels of Col1A1 as compared to individual compounds. In conclusion, the ion-pairing nanocomplex of CTX-MEL represents a promising carrier that can be topically applied to improve wound healing.